2018
DOI: 10.1186/s12934-018-0893-z
|View full text |Cite
|
Sign up to set email alerts
|

Torulene and torularhodin: “new” fungal carotenoids for industry?

Abstract: Torulene and torularhodin represent the group of carotenoids and are synthesized by yeasts and fungi. The most important producers of these two compounds include yeasts of Rhodotorula and Sporobolomyces genera. The first reports confirming the presence of torulene and torularhodin in the cells of microorganisms date to the 1930s and 1940s; however, only in the past few years, the number of works describing the properties of these compounds increased. These compounds have strong anti-oxidative and anti-microbia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(100 citation statements)
references
References 103 publications
(131 reference statements)
1
90
0
9
Order By: Relevance
“…Furtherly, it was confirmed that both of them facilitated protective activity on human prostate stromal cells from oxidative stress damage [22]. Meanwhile, the anti-microbial activity of the two carotenoids had also been confirmed, which revealed their potential usage on infection prevention particularly in implanted medical products and preparations that require natural antimicrobials (Kot et al, 2018) [11]. Lastly, torularhodin is one of the few carotenoids with carboxylic acid function [19].…”
Section: Torulene and Torularhodinmentioning
confidence: 97%
See 1 more Smart Citation
“…Furtherly, it was confirmed that both of them facilitated protective activity on human prostate stromal cells from oxidative stress damage [22]. Meanwhile, the anti-microbial activity of the two carotenoids had also been confirmed, which revealed their potential usage on infection prevention particularly in implanted medical products and preparations that require natural antimicrobials (Kot et al, 2018) [11]. Lastly, torularhodin is one of the few carotenoids with carboxylic acid function [19].…”
Section: Torulene and Torularhodinmentioning
confidence: 97%
“…These approaches allowed the conclusion that the genus Rhodotorula possesses an identical or conserved carotenoid biosynthetic pathway ( Fig. 2) [10,11]. Carotenoid biosynthesis is known to follow the consecutive condensations of isoprenoid units into phytoene, the first colorless carotenoid in the pathway.…”
Section: Biosynthetic Pathway Of Carotenoids In Rhodotorulamentioning
confidence: 99%
“…Many yeasts in the Pucciniomycotina accumulate carotenoid pigments, thus earning the common name ‘red yeasts’. Several others also accumulate lipids or possess metabolic capabilities that are not common within Saccharomycotina (Frengova & Beshkova, ; Ageitos et al, ; Kot et al, ). These traits have raised considerable interest for their possible industrial applications.…”
Section: The Yeast Lifestylementioning
confidence: 99%
“…[23,24]. In recent years, there have been increasing studies related to torularhodin and torulene biosynthesis and applications [25]. Fig.…”
Section: Isolation Of R Toruloides Rm11 Rm14 and Rm18mentioning
confidence: 99%
“…It has been reported that torularhodin and torulene are mainly accumulated in yeasts of Rhodotorula and Sporobolomyces genera [23,25]. Very few reports are available on torularhodin and torulene production from Rhodosporidium genera.…”
Section: Isolation Of R Toruloides Rm11 Rm14 and Rm18mentioning
confidence: 99%